Antimalarial activity screening from endophytic fungus of red ginger (Zingiber officinale): in vitro and in silico studies - Artasasta, Muh Ade; Faradilla, Diandra Mytha; Rasyid, Herlina; Listyorini, Dwi; Putra, Wira Eka; Handayani, Dian; Riga, Riga; Kuo, Ping-Chung; Li, Hao-Ze; Chang, Pei-Hung; Fitri, Loeki Enggar; Harwoko, Harwoko; et al. (Penerbit Universiti Kebangsaan Malaysia, 2025)
Diversity exploration of secondary metabolite compounds from plant endophytic fungi is expected to yield novel compounds that can efficiently overcome Plasmodium resistance. This study aimed to assess the antimalarial activity of the endophytic fungus derived from red ginger Zingiber officinale against Plasmodium berghei. Subsequently, the endophytic fungus was isolated from the sample using the dilution method, followed by evaporation. Nine isolates of endophytic fungi were successfully isolated that were assigned as JMR1, JMR2, JMR3, JMR5, JMB1, JMB2, JMB3, JMD1, and JMD2. The antimalarial efficacy showed that the JMR5 isolate exhibited significant activity in suppressing the proliferation of P. berghei. This activity was quantified by a per cent inhibition of 83.01% and an IC50 value of 5.81 μg/mL. The detected antimalarial activity of the JMR5 extract can be related to the presence of several phytochemicals, including alkaloids, flavonoids, and terpenoids. In addition, molecular identification was conducted using ITS primers on the JMR5 isolate, showing a complete genetic similarity of 100% with Aspergillus flavus. GNPS analysis was conducted using LCMS-MS data on ethyl acetate extract. Surafactin c, surafactin c14 and erucamide were probably secondary metabolites in the JMR5 extract. Furthermore, drug-likeness and molecular docking analysis were conducted. The result showed that erucamide is a potential antimalarial due to the fulfil of Lipinski’s rule of five and also the binding affinity (- 4.2 kcal/mol) against Plasmepsin I. Based on the results obtained, the development of secondary metabolites from Aspergillus flavus JMR5 as potential antimalarial compounds is important to carry out.